First‐line immune checkpoint therapy in metastatic squamous cell lung cancer harboring both EGFR mutation and high expression of PD‐L1: A case report. Issue 6 (14th April 2020) - Hamai, Kosuke; Tanahashi, Hiroki; Ueno, Sayaka; Konishi, Hanae; Matsumura, Mirai; Nomura, Akio; Nakamoto, Kanako; Isoyama, Shoko; Tanimoto, Takuya; Shoda, Hiroyasu; Ishikawa, Nobuhisa
Abstract : A 90‐year‐old female was admitted to our hospital with a history of a dry cough. Chest computed tomography (CT) scan showed a tumor shadow, and CT‐guided lung biopsy revealed squamous cell carcinoma harboring an EGFR mutation. In addition, programmed death‐ligand 1 (PD‐L1) was highly expressed with a tumor proportion score (TPS) of >75%. Pembrolizumab therapy in the first‐line setting was not effective, and the patient died at six months from the first visit. Squamous cell lung cancers (SCLCs) with both EGFR mutation and high expression of PD‐L1 are very rare.